Child Health Trends in Central and Eastern Europe - Bruno Jacques Martin (Paediatrica Indonesiana, 1996)
Overall Health ConditionsThe well-known events that resulted in worsening economic and social conditions all over Europe after 1989, led to a parallel decline in health, which deteriorated only moÂ¬derately in central and some parts of eastern Europe1 during transition, but suffered a decline as severe as has never been witnessed in times of peace in other countries and especially in Russia and Ukraine. The dramatic rise in mortality recorded since 1989 has been selective, sparing women more than men, affecting the young and the eldÂ¬erly only moderately but taking a severe toll especially among men of working age. Deaths of males aged 20 to 39 in Russia rose by no less than 70% between 1989 and 1993, and by over 50% in the 40 to 59 group. The rise in Ukraine was a uniform 30% for both groups over this period. It was smaller, though still significant, elsewhere, for example about 11% overall in Bulgaria, 15% in Romania, 8% in Poland.